Water-based high-permeability multifunctional toning primer
By using water-based high-permeability multi-functional color-to-tuning primer in exterior wall coatings, the combination of small-particle and large-particle styrene acrylic emulsions is solved, and the problem of insufficient adhesion performance of the coating on the loose bottom surface is achieved, and better film formation and resistance are achieved.
Patent Information
- Application Number
- CN202510150049.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-11
- Publication Date
- 2025-04-25
AI Technical Summary
The adhesion performance and stability of existing exterior wall coatings on loose bottom surfaces are difficult to improve, resulting in insufficient film formation and resistance of the coating.
The water-based high-permeability multi-functional color-to-tune primer is used to improve the permeability, film-forming and resistance of the primer by combining small-particle and large-particle styrene acrylic emulsion, combined with pigment fillers and additives.
It improves the adhesion and stability of the primer, enhances the water and alkali resistance of the coating, and can effectively fix the dust on the loose bottom surface, improving the overall performance of the coating.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the field of exterior wall coatings, and in particular to a water-based high-penetration multifunctional color-adjusting primer. Background Art
[0002] Exterior wall paint is a primer used for the exterior walls of buildings. Its main function is to protect the sealing layer, which can improve the adhesion of the paint, increase the fullness of the topcoat, and provide alkali resistance and anti-corrosion capabilities. It can effectively seal the concrete substrate and prevent bubbles, rust and falling off on the wall, thereby protecting the exterior walls of the building from environmental influences.
[0003] When painting exterior walls, the condition of the wall is also an important factor affecting the stability of the paint. When the bottom surface of the wall is too loose, it becomes difficult for the primer to penetrate into the wall base material. After the primer forms a film, the stability of adhesion to the wall surface is difficult to improve. Summary of the invention
[0004] In order to improve the adhesion performance of the primer, the present application provides a water-based high-penetration multifunctional color-adjusting primer.
[0005] The present application provides a water-based high-penetration multifunctional color-adjusting primer using the following technical solution: A water-based high-penetration multifunctional color-adjusting primer comprises a styrene-acrylic emulsion, a pigment filler, cellulose, an additive, and deionized water; the styrene-acrylic emulsion comprises a small-particle styrene-acrylic emulsion and a large-particle styrene-acrylic emulsion, the mass ratio of the small-particle styrene-acrylic emulsion to the large-particle styrene-acrylic emulsion is (0.5-2):1, and the large-particle styrene-acrylic emulsion comprises any one or more groups of styrene, acrylonitrile, and epoxy groups.
[0006] By adopting the above technical scheme, emulsions with large and small particle sizes can adapt to the construction of complex wall conditions. When the construction base is loose, the small-particle styrene acrylic emulsion can penetrate into the base material for reinforcement. When the construction base is dense and has a certain strength, the primer forms a dense and uniform coating on the base coating through the combination of large and small particle sizes of styrene acrylic emulsions, and can mask the base through pigments and fillers, so that the primer can better adhere to the construction base, thereby improving the stability of the primer after coating.
[0007] Preferably, the particle size of the small-particle styrene-acrylic emulsion is 60-100 μm, and the particle size of the large-particle styrene-acrylic emulsion is 100-250 μm.
[0008] By adopting the above technical solution, styrene acrylic emulsions of different particle sizes are matched. Small-particle latex particles below 100μm can achieve penetration function, and large-particle styrene acrylic emulsions of 100μm-250μm can achieve film-forming properties and resistance to primer coatings.
[0009] Preferably, the pigment and filler include any one or more mixtures of graphene, graphene oxide composite components, titanium dioxide, barium sulfate, silicon dioxide powder, and calcium carbonate powder.
[0010] Preferably, the auxiliary agent includes any one or more of a wetting agent, a dispersant, a defoaming agent, a bactericide, an antifreeze agent, a leveling agent, a reinforcing agent, a pH regulator, and a thickener.
[0011] By adopting the above technical solution, through the combination of pigments and fillers with the wetting agent in the additive, it is possible to provide more sufficient spreading and wetting for the coating, and to form good spreading and adhesion for the uneven surface of the old coating film and the residual surface energy of the old coating film.
[0012] Preferably, the reinforcing agent comprises any one or more of isocyanate, aziridine, epoxy silane and melamine.
[0013] By adopting the above technical solution, after the above reinforcing agent is added, the cross-linking density between the segments of the emulsion system can be increased, thereby improving the water resistance and alkali resistance of the coating film after the primer is formed.
[0014] Preferably, the graphene oxide composite component comprises graphene oxide, modified chitosan and modified nano-silicon dioxide.
[0015] By adopting the above technical scheme, graphene oxide is a two-dimensional lamellar structure, which can achieve anti-corrosion performance in the coating. Nano-silicon dioxide has the properties of small particle size, low density, large specific surface area, and also has corrosion resistance. The dispersibility of modified silicon dioxide is improved, so that silicon dioxide is more evenly dispersed in the system. Through the combination of modified chitosan, graphene and modified nano-silicon dioxide, the prepared graphene oxide composite components can be combined to obtain a stable network structure, so that the density of the coating is improved, and the mechanical strength of the overall corrosion resistance of the coating is improved.
[0016] Preferably, the modified chitosan is prepared by the following method: After the chitosan is dried, it is added into water, subjected to ultrasonic oscillation and then magnetic stirring to obtain a chitosan solution. Glacial acetic acid is added into the chitosan solution, stirred for reaction, washed and dried to obtain modified chitosan.
[0017] By adopting the above technical solution, H in glacial acetic acid + It can protonate -NH2 in chitosan to -NH3 + , destruction, so that chitosan can be evenly dispersed in the system, thereby improving the overall stability of the system.
[0018] Preferably, the modified silicon dioxide raw material comprises nano silicon dioxide and a silane coupling agent, and the modified silicon dioxide is prepared by the following method: The nano silicon dioxide powder is dried, mixed with a silane coupling agent, anhydrous ethanol and water under magnetic stirring, centrifuged and vacuum dried to obtain modified nano silicon dioxide.
[0019] Preferably, the mass ratio of the silicon dioxide to the silane coupling agent is 1:(3.2-3.4).
[0020] By adopting the above technical solution, preferably the mass ratio between silicon dioxide and the silane coupling agent is within the above range, which can further improve the stability of the prepared modified silicon dioxide.
[0021] Preferably, the mass ratio of the graphene oxide, modified chitosan and modified nano-silicon dioxide is (2.2-2.4):4.3:1.
[0022] By adopting the above technical solution, preferably the mass ratio of graphene oxide, modified chitosan and modified nano-silicon dioxide is within the above range, which can further improve the stability of the prepared graphene oxide composite component.
[0023] In summary, the present application includes at least one of the following beneficial technical effects: 1. Through the combination of large-particle styrene acrylic emulsion and small-particle styrene acrylic emulsion, the small-particle styrene acrylic emulsion can improve the overall permeability of the primer, and the large-particle styrene acrylic emulsion can improve the film-forming property and resistance of the primer. At the same time, the large-particle styrene acrylic emulsion improves the encapsulation performance of the pigment and filler, and after film formation, it can improve the corresponding water resistance, alkali resistance, hydrochloric acid mist resistance and other coating resistance, as well as the fixation performance of the loose construction bottom surface dust during the film formation process, so that the adhesion of the primer after film formation is improved; 2. When the bottom surface of the construction wall is relatively loose, the small-particle styrene acrylic emulsion can penetrate into the base material for reinforcement. When the bottom surface of the construction wall is dense and has a certain strength, the primer forms a relatively dense and uniform coating on the construction wall coating by matching large and small particle sizes, and the construction wall is shielded by pigments and fillers; 3. Graphene, talcum powder, etc., combined with wetting agents, provide sufficient spreading and wetting for the coating, which can form good spreading and adhesion on the uneven surface of the old coating on the construction wall and the old coating with a higher residual surface; 4. Titanium dioxide, barium sulfate powder and the like can provide good hiding power, and the reinforcing agent can improve the cross-linking density of the primer system emulsion, thereby further improving the water and alkali resistance of the coating. DETAILED DESCRIPTION
[0024] The present application is further described in detail below with reference to the embodiments: Raw material description: All raw materials in the examples can be obtained from the market; the particle size of the small-particle styrene acrylic emulsion is 60-100 μm. The particle size of the large-particle styrene acrylic emulsion is 100-250 μm; the pH regulator is AMP-950; the wetting agent is wetting agent HY-1608; the dispersant is BYK110; the film-forming aid is propylene glycol methyl ether acetate; the antifreeze agent is ethylene glycol; the defoamer is BYK-051; the bactericide is glutaraldehyde; the mildewproof agent is isopropyl alcohol; the leveling agent is fatty alcohol polyoxyethylene ether; the enhancer is prepared by mixing cyanate, aziridine, epoxy silane, and melamine in equal proportions; the thickener is thickener TT-936.
[0025] Example 1 Prepare the primer: The following substances are mixed according to the mass ratio to obtain the primer: Deionized water 13.53%, cellulose ether 0.2%, pH adjuster 0.3%, wetting agent 0.1%, dispersant 0.25%, defoamer 0.1%, graphene 0.02%, titanium dioxide 12%, silica powder 3%, kaolin 5%, talc 5%, small particle size styrene acrylic emulsion 25%, large particle size styrene acrylic emulsion 30%, film-forming aid 2.0%, antifreeze 0.8%, defoamer 0.1%, bactericide 0.3%, mildewproofing agent 0.5%, leveling agent 0.5%, enhancer 0.6%, thickener 0.2%, anionic water-based color paste 0.5%.
[0026] Example 2 The following substances are mixed according to the mass ratio to obtain the primer: Deionized water 16.43%, cellulose ether 0.3%, pH adjuster 0.3%, wetting agent 0.1%, dispersant 0.25%, defoamer 0.1%, graphene 0.02%, titanium dioxide 5%, barium sulfate 12%, calcium carbonate 5%, small particle size styrene acrylic emulsion 20%, large particle size styrene acrylic emulsion 35%, film-forming aid 1.8%, antifreeze 0.8%, defoamer 0.1%, bactericide 0.3%, mildewproofing agent 0.5%, leveling agent 0.3%, enhancer 0.5%, thickener 0.2%, anionic water-based color paste 1.0%.
[0027] Example 3 The following substances are mixed according to the mass ratio to obtain the primer: Deionized water 8.5%, cellulose ether 0.15%, pH adjuster 0.3%, wetting agent 0.1%, dispersant 0.25%, defoamer 0.1%, graphene 0.05%, titanium dioxide 20%, silica powder 4.95%, small particle size styrene acrylic emulsion 40%, large particle size styrene acrylic emulsion 20%, film-forming aid 3.0%, antifreeze 0.8%, defoamer 0.1%, bactericide 0.3%, mildewicide 0.5%, leveling agent 0.2%, enhancer 0.3%, anionic water-based color paste 0.4%.
[0028] Example 4 Preparation of modified chitosan: 4.5 parts of chitosan were dried in a vacuum drying oven at 30°C for 6 hours, and then the dried chitosan was added to 100 parts of distilled water, ultrasonically oscillated for 2 hours, and then magnetically stirred at 50°C for 3 hours to obtain a chitosan solution, 0.05 parts of glacial acetic acid were added to the chitosan solution, stirred for reaction, washed with ethanol, and dried to obtain modified chitosan.
[0029] Preparation of graphene oxide composite components: 6 parts of nano-silica powder were dried in a vacuum drying oven at 50°C for 6 hours, then mixed with 19.2 parts of KH550, 50 parts of anhydrous ethanol and 50 parts of deionized water, magnetically stirred at 90°C for 3 hours, centrifuged and vacuum dried to obtain modified nano-silica; modified chitosan, modified nano-silica and graphene oxide were mixed in a mass ratio of 2.2:4.4:1 to obtain a graphene oxide composite component.
[0030] The following substances are mixed according to the mass ratio to obtain the primer: Deionized water 8.5%, cellulose ether 0.15%, pH adjuster 0.3%, wetting agent 0.1%, dispersant 0.25%, defoamer 0.1%, graphene oxide composite component 5%, titanium dioxide 20%, small particle size styrene acrylic emulsion 40%, large particle size styrene acrylic emulsion 20%, film-forming aid 3.0%, antifreeze 0.8%, defoamer 0.1%, bactericide 0.3%, mildewicide 0.5%, leveling agent 0.2%, enhancer 0.3%, anionic water-based color paste 0.4%.
[0031] Example 5 Preparation of modified chitosan: 4.5 parts of chitosan were dried in a vacuum drying oven at 30°C for 6 hours, and then the dried chitosan was added to 100 parts of distilled water, ultrasonically oscillated for 2 hours, and then magnetically stirred at 50°C for 3 hours to obtain a chitosan solution, 0.05 parts of glacial acetic acid were added to the chitosan solution, stirred for reaction, washed with ethanol, and dried to obtain modified chitosan.
[0032] Preparation of graphene oxide composite components: 6 parts of nano-silica powder were dried in a vacuum drying oven at 50°C for 6 hours, then mixed with 20.4 parts of KH550, 50 parts of anhydrous ethanol and 50 parts of deionized water, magnetically stirred at 90°C for 3 hours, centrifuged and vacuum dried to obtain modified nano-silica; modified chitosan, modified nano-silica and graphene oxide were mixed in a mass ratio of 2.4:4.3:1 to obtain a graphene oxide composite component.
[0033] The following substances are mixed according to the mass ratio to obtain the primer: Deionized water 8.5%, cellulose ether 0.15%, pH adjuster 0.3%, wetting agent 0.1%, dispersant 0.25%, defoamer 0.1%, graphene oxide composite component 5%, titanium dioxide 20%, small particle size styrene acrylic emulsion 40%, large particle size styrene acrylic emulsion 20%, film-forming aid 3.0%, antifreeze 0.8%, defoamer 0.1%, bactericide 0.3%, mildewicide 0.5%, leveling agent 0.2%, enhancer 0.3%, anionic water-based color paste 0.4%.
[0034] Example 6 Preparation of modified chitosan: 4.5 parts of chitosan were dried in a vacuum drying oven at 30°C for 6 hours, and then the dried chitosan was added to 100 parts of distilled water, ultrasonically oscillated for 2 hours, and then magnetically stirred at 50°C for 3 hours to obtain a chitosan solution, 0.05 parts of glacial acetic acid were added to the chitosan solution, stirred for reaction, washed with ethanol, and dried to obtain modified chitosan.
[0035] Preparation of graphene oxide composite components: 6 parts of nano-silica powder were dried in a vacuum drying oven at 50°C for 6 hours, then mixed with 19.8 parts of KH550, 50 parts of anhydrous ethanol and 50 parts of deionized water, magnetically stirred at 90°C for 3 hours, centrifuged and vacuum dried to obtain modified nano-silica; modified chitosan, modified nano-silica and graphene oxide were mixed in a mass ratio of 2.3:4.3:1 to obtain a graphene oxide composite component.
[0036] The following substances are mixed according to the mass ratio to obtain the primer: Deionized water 8.5%, cellulose ether 0.15%, pH adjuster 0.3%, wetting agent 0.1%, dispersant 0.25%, defoamer 0.1%, graphene oxide composite component 5%, titanium dioxide 20%, small particle size styrene acrylic emulsion 40%, large particle size styrene acrylic emulsion 20%, film-forming aid 3.0%, antifreeze 0.8%, defoamer 0.1%, bactericide 0.3%, mildewicide 0.5%, leveling agent 0.2%, enhancer 0.3%, anionic water-based color paste 0.4%.
[0037] Example 7 Example 7 is based on Example 6. When preparing nano-silicon dioxide in Example 7, 18 parts of KH550 are used.
[0038] Example 8 Example 8 is based on Example 6. When preparing modified nano-silica in Example 8, 21.6 parts of KH550 are used.
[0039] Example 9 Example 9 is based on Example 6. When preparing the graphene oxide composite component in Example 6, the mass ratio of modified chitosan, modified nano-silicon dioxide and graphene oxide is 2:4.3:1.
[0040] Example 10 Example 10 is based on Example 6. When preparing the graphene oxide composite component in Example 10, the mass ratio of modified chitosan, modified nano-silicon dioxide and graphene oxide is 2.6:4.3:1.
[0041] Embodiment 11 Example 11 is based on Example 6. In Example 11, when preparing the graphene oxide composite component, the modified chitosan is replaced with ordinary chitosan.
[0042] Example 12 Example 12 is based on Example 6. In Example 12, when preparing the graphene oxide composite component, the modified nano-silicon dioxide is replaced with ordinary silicon dioxide.
[0043] Comparative Example 1 The following substances are mixed according to the mass ratio to obtain the primer: Deionized water 23.2%, cellulose ether 0.5%, pH adjuster 0.1%, wetting agent 0.2%, dispersant 0.4%, defoamer 0.2%, titanium dioxide 5%, barium sulfate 5%, calcium carbonate 10%, kaolin 7%, other powders 3%, other emulsions 40%, film-forming aid 2.0%, antifreeze 0.5%, defoamer 0.1%, bactericide 0.3%, thickener 0.5%, anionic water-based color paste 2.0%.
[0044] Among them, other powders are mica powders, and other emulsions are silicone-acrylic emulsions.
[0045] Performance testing The following performance tests were performed on Examples 1-11 and Comparative Example 1: Using "JG / T 210-2018" as the detection method, the contrast ratio, salt and alkali resistance, reinforcement performance, and water permeability of the samples were tested, and the adhesion test was carried out according to "GB / T 9753-2007 Coating Performance Test Adhesion Test".
[0046] Table 1 Performance test results of Examples 1-11 and Comparative Example 1 It can be seen from Table 1 that the tinting primer prepared in the present application has good adhesion performance, and has good fixing performance and coating resistance.
[0047] In Examples 4 to 6, a graphene oxide composite component is further added to the pigment filler, which can further improve the corrosion resistance of the obtained coating and enhance the bonding performance between the various components, thereby improving the overall performance of the coating.
[0048] In Example 7 and Example 8, when preparing modified nano-silica, the mass ratio of nano-silica to KH550 is not within the range specified in the present application. When the content of KH550 is too little, the modification effect of nano-silica is difficult to be further improved, the compatibility of nano-silica in the system is difficult to be further improved, and the dispersibility and binding performance are reduced, which affects the comprehensive performance of Example 8; when the content of KH550 is too much, too much KH550 accumulates on the surface after hydrolysis, and the viscosity of nano-silica is too large, which affects the overall stability of the system. Therefore, the various performances of Example 8 and Example 9 are affected.
[0049] In Example 9 and Example 10, when preparing the graphene oxide composite component, the mass ratios of modified chitosan, modified nano-silica and graphene oxide are not within the range specified in the present application. When the content of graphene oxide is too much or too little, it is difficult to form a stable cross-linked three-dimensional network structure between modified chitosan, modified nano-silica and graphene oxide, and it is difficult to further improve the corrosion resistance of the coating formed by the primer. At the same time, the stability is also affected. The comprehensive performance of Example 9 and Example 10 is reduced.
[0050] In Example 11, the modified chitosan is replaced by ordinary chitosan. The unmodified chitosan is difficult to further cross-link with graphene oxide. Therefore, the binding performance of the graphene oxide composite component prepared in Example 11 is reduced, affecting the overall comprehensive performance of the system.
[0051] In Example 12, the modified nano-silica was replaced with ordinary nano-silica. The dispersibility of the unmodified nano-silica was difficult to improve and agglomeration occurred in the system, which affected the stability of the system. Therefore, the overall performance of Example 12 was reduced.
[0052] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A water-based high-penetration multifunctional toning primer, characterized in that: Including styrene acrylic emulsion, pigments and fillers, cellulose, additives, and deionized water; The styrene acrylic emulsion includes a small-particle styrene acrylic emulsion and a large-particle styrene acrylic emulsion, the mass ratio of the small-particle styrene acrylic emulsion to the large-particle styrene acrylic emulsion is (0.5-2):1, and the large-particle styrene acrylic emulsion includes any one or more groups of styrene, acrylonitrile, and epoxy groups.
2. The water-based high-penetration multifunctional toning primer according to claim 1, characterized in that: The particle size of the small-particle styrene-acrylic emulsion is 60-100 μm, and the particle size of the large-particle styrene-acrylic emulsion is 100-250 μm.
3. The water-based high-penetration multifunctional toning primer according to claim 1, characterized in that: The pigment and filler include any one or more mixtures of graphene, graphene oxide composite components, titanium dioxide, barium sulfate, silicon dioxide powder, and calcium carbonate powder.
4. The water-based high-penetration multifunctional toning primer according to claim 1, characterized in that: The auxiliary agent includes any one or more of a wetting agent, a dispersant, a defoamer, a bactericide, an antifreeze agent, a leveling agent, a reinforcing agent, a pH regulator, and a thickener.
5. The water-based high-penetration multifunctional toning primer according to claim 4, characterized in that: The reinforcing agent includes any one or more of isocyanate, aziridine, epoxy silane and melamine.
6. The water-based high-penetration multifunctional toning primer according to claim 1, characterized in that: The graphene oxide composite component comprises graphene oxide, modified chitosan and modified nano silicon dioxide.
7. The water-based high-penetration multifunctional toning primer according to claim 6, characterized in that: The modified chitosan is prepared by the following method: After the chitosan is dried, it is added into water, subjected to ultrasonic oscillation and then magnetic stirring to obtain a chitosan solution. Glacial acetic acid is added into the chitosan solution, stirred for reaction, then washed and dried to obtain modified chitosan.
8. The water-based high-penetration multifunctional toning primer according to claim 6, characterized in that: The modified silicon dioxide raw material includes nano silicon dioxide and a silane coupling agent, and the modified silicon dioxide is prepared by the following method: The nano silicon dioxide powder is dried, mixed with a silane coupling agent, anhydrous ethanol and water under magnetic stirring, centrifuged and vacuum dried to obtain modified nano silicon dioxide.
9. The water-based high-penetration multifunctional toning primer according to claim 8, characterized in that: The mass ratio between the silicon dioxide and the silane coupling agent is 1:(3.2-3.4).
10. The water-based high-penetration multifunctional toning primer according to claim 6, characterized in that: The mass ratio of the graphene oxide, the modified chitosan and the modified nano-silicon dioxide is (2.2-2.4):4.3:1.